Analysis of Smallholders' Progress in Implementing Sustainable Management in North Sumatra, Indonesia - Chalil, Diana; Barus, Riantri (Indonesian Journal of Agricultural Research, 2018)
The significant increase in oil palm areas has resulted in more concerns to the environmental issues - as majority of farming activities were not conducted in sustainable ways. To address the environmental issues, the Roundtable Sustainable Palm Oil (RSPO) organization has formulated principles and criterias (PnC) for sustainable practices of the oil palm plantation as a guideline, whereby it has to be adhered by all parties involved, including the smallholders. The study is therefore conducted to analyze the sustainable management implementation among smallholders in North Sumatra. In total, 320 and 137 schemed and independent smallholders from four oil palm plantations centers in North Sumatra were interviewed in 2012 and 2018 to see their progress. The levels of implementation for each group were determined based on their scores for each of the criteria, and were compared with the independent sample t-test. The influencing factors for implementation levels were estimated by using multinomial logit model. The results showed that the level of implementation for both schemed and independent smallholders were still low in both 2012 and 2018. Education, experience and participation were identified as factors that significantly influenced their sustainable management implementation levels. Therefore, it is suggested that trainings should be emphasized to improve the sustainable management implemenatation among oil palm smallholders.